PERAN KOMUNIKASI BUDAYA DALAM UPAYA PELESTARIAN MELALUI WORKSHOP BATIK TRADISIKU BOGOR THE ROLE OF CULTURAL COMMUNICATION IN PRESERVATION EFFORTS THROUGH THE BATIK TRADISIKU BOGOR WORKSHOP - Rahayu, Aprilia Ajeng; Nuraeni, Yeni (Lembaga Penerbitan Universitas Esa Unggul, 2026)
This study aims to examine the role of batik workshops as a medium of communication in preserving local culture in the city of Bogor. The research focuses on Batik Tradisiku Bogor as a cultural actor that actively introduces traditional batik values through workshop activities. This study employs a qualitative research approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation involving workshop organizers and participants. The results show that batik workshops function not only as educational activities but also as effective cultural communication media that convey cultural values, symbols, and meanings of batik to the community. Through interactive communication processes, participants gain knowledge, cultural awareness, and appreciation of batik as part of Indonesia’s cultural heritage. The study concludes that batik workshops play a significant role in supporting cultural preservation efforts by fostering cultural understanding and encouraging community participation in maintaining traditional cultural practices.Keywords: Batik Workshop, Cultural Communication, Cultural Preservation